All in a lifetime : an autobiography - Westheimer, Ruth K. 1928- (Warner, 1987)
To the world, she is everyone's favorite sex therapist; a four-foot-seven-inch dynamo who answers our most intimate questions with disarming candor and heartening warmth. Yet few people know the real Dr. Ruth -- her loves, her losses, and the irrepressible spirit that has helped her through it all. Here, for the first time ever, Dr. Ruth opens her heart ... and the pages of her girlhood diaries to share her remarkable life story. Meet the child orphaned by the Holocaust, the Israeli soldier wounded on her twentieth birthday, and the citizen of the world who has called five countries home. A revealing autobiography of a fighter who has survived heartache with her spirit intact, All in a Lifetime offers a close and personal look at a courageous and very loving woman.